Discovery of ruthenium(ii) metallocompound and olaparib synergy for cancer combination therapy - Yusoh, Nur Aininie; Tiley, Paul R.; James, Steffan D.; Harun, Siti Norain; Thomas, Jim A.; Saad, Norazalina; Ling, Wei Hii; Suet, Lin Chia; Gill, Martin R.; Ahmad, Haslina (American Chemical Society, 2023)
Synergistic drug combinations can extend the use of poly(ADP-ribose) polymerase inhibitors (PARPi) such as Olaparib to BRCA-proficient tumors and overcome acquired or de novo drug resistance. To identify new synergistic combinations for PARPi, we screened a “micro-library” comprising a mix of commercially available drugs and DNA-binding ruthenium(II) polypyridyl complexes (RPCs) for Olaparib synergy in BRCA-proficient triple-negative breast cancer cells. This identified three hits: the natural product Curcumin and two ruthenium(II)-rhenium(I) polypyridyl metallomacrocycles. All combinations identified were effective in BRCA-proficient breast cancer cells, including an Olaparib-resistant cell line, and spheroid models. Mechanistic studies indicated that synergy was achieved via DNA-damage enhancement and resultant apoptosis. Combinations showed low cytotoxicity toward non-malignant breast epithelial cells and low acute and developmental toxicity in zebrafish embryos. This work identifies RPC metallomacrocycles as a novel class of agents for cancer combination therapy and provides a proof of concept for the inclusion of metallocompounds within drug synergy screens.